The "politics of method" in volatile settings: research with mobile workers in rural resource regions. Issue 4 (2nd October 2022) - Ryser, Laura; Halseth, Greg; Markey, Sean
ABSTRACT: Research in contentious and fluctuating political and economic conditions presents many challenges. Given the potential for the politicization of research in an era where information is rapidly changing, there is pressure to consider pathways to ensure quality and transparent research. This perspective builds upon a tradition of considering the methodological implications associated with conducting research within volatile settings. The paper reflects on the research process associated with interviewing mobile workers at BC Hydro's Site C Project (hydroelectric dam) in northeast British Columbia, Canada. Based on these reflections, we explore opportunities to extend the transparency of research in volatile settings by considering the broader political and subjective influences that shape credibility and validity as universities, industry, and labour engage with the research process.